Defect observations of Ni/AlGaN/GaN Schottky contacts on Si substrates using scanning internal photoemission microscopy. (21st February 2018) - Shiojima, Kenji; Konishi, Hiroaki; Imadate, Hiroyoshi; Yamaoka, Yuya; Matsumoto, Kou; Egawa, Takashi
Abstract: We have demonstrated the use of scanning internal photoemission microscopy (SIPM) to characterize crystal defects in an AlGaN/GaN heterostructure grown on Si substrates. SIPM enabled the visualization of unusually grown regions owing to cracking of the Si substrates. In these regions, photocurrent was large, which was consistent with leaky current–voltage characteristics. We also found smaller photoyield regions, which may originate from the Al-rich AlGaN regions on hillocks. We confirmed the usefulness of SIPM for investigating the inhomogeneity of crystal quality and electrical characteristics from macroscopic viewpoints.